Optimization of inter-layer printing parameters for enhanced mechanical performance of PETG in fused deposition modeling (FDM) - Kumaresan, Rajan; Kadirgama, Kumaran; Samykano, Mahendran; Wan Sharuzi, Wan Harun; Thirugnanasambandam, Arunkumar; Aslfattahi, Navid; Samylingam, Lingenthiran; Kok, Chee Kuang; Mohd fairusham, ghazali (Elsevier B.V., 2025)
Fused deposition modeling (FDM) has emerged as a cost-effective and extremely productive method among the 3D printing methods. Although significant efforts have been made to improve the quality of FDM products, there are still obstacles in terms of material availability and quality compared to traditional methods. This study focused on enhancing the mechanical characteristics of the Polyethylene terephthalate glycol (PETG) by varying the infill pattern and raster angle of the top/bottom and intermittent layers. The response surface methodology technique was initially used for optimization then statistical analysis was conducted using the experimental data. The maximum tensile characteristics of 48.19 MPa were achieved in the PETG specimens with inter-layered parameters. This was seen in the inner infill pattern of rectilinear, inner raster of 45◦, and the top/bottom infill pattern of concentric with the top/bottom raster angle of 90◦. The specimen’s maximum compressive strength, determined to be 22.64 MPa, is achieved through the use of a rectilinear inner infill and a 0◦ inner raster, combined with a rectilinear top/bottom infill pattern and a 45◦ top/bottom raster. Moreover, the percentage of error between the predicted and experimental data was below 5 %, indicating that the regression values are satisfactory